Effectiveness of the Role of the East Java KPU's Information and Legal Documentation Network (JDIH) in Transparency and Monitoring of the 2024 East Java Regional Elections - Octavia, Aisyah Retno; Nawangsari, Ertien Rining (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
This study aims to analyze the role of the East Java KPU Legal Documentation and Information Network (JDIH) in supporting transparency and supervision of the 2024 East Java Pilkada. Limited access to legal information is often an obstacle to realizing accountability and transparency in elections. Through the existence of the East Java KPU JDIH, legal information related to the Pilkada, such as KPU regulations, decisions, and technical guidelines, can be easily accessed by the public, Pilkada participants, and other stakeholders. This study uses a qualitative methodology with a descriptive approach to examine the effectiveness of JDIH in supporting information disclosure. The results of the study show that the East Java KPU JDIH has succeeded in providing accurate, easily accessible legal information and supporting transparency in the Pilkada stages. By utilizing digital platforms and social media, the East Java KPU JDIH has also accelerated the distribution of information related to the 2024 Pilkada. In addition, the management of JDIH involving competent human resources and structured internal processes contributes to the effectiveness of the management and dissemination of legal information. JDIH KPU East Java plays an important role in ensuring more active public participation and facilitating more transparent and accountable Pilkada monitoring.